ON THE NORMATIVE FUNDING OF HIGHER EDUCATION: CURRENT STATE AND DEVELOPMENT TRENDS - N. M. Rosina; V. M. Zuev (Финансы: теория и практика, 2017)
The paper continues the authors’ publication in the Bulletin of Financial University (2015, No. 3) and discusses the current situation with the budget financing of higher education based on the per capita funding standards as well as the international experience in this field. The authors analyze the main financial indices of the higher education in Russia and developed countries in the context of the general conditions of its financial basis. The disproportions between the sizes of the current standards of the per capita budget funding and the actual costs of training an individual student at Russian universities are revealed; the ways to optimize the needed cost estimations for higher education and improvement of the appropriate standards development are considered.